The Heliconoides Modified Dissolution Index-HMDI: Do methane seepage environments affect the preservation state of Heliconoides inflatus? - Beccari, Valentina; Almogi-Labin, Ahuva; Basso, Daniela; Panieri, Giuliana; Makovsky, Yizhaq; Neururer, Christoph; Hajdas, Irka; Spezzaferri, Silvia (Elsevier, 2023)
Pteropods are holoplanktonic molluscs presently endangered because their fragile aragonitic shell is very sensitive to ocean acidification. The preservation of pteropods, and in particular of the mesopelagic Heliconoides (Limacina) inflatus, has been used to assess aragonite saturation state in Quaternary sediments (Limacina Dissolution Index, LDX) as an inferred proxy for climatic changes. Three deep-sea cores retrieved in 2016 during the EUROFLEETS2 SEMSEEP cruise offshore Israel are investigated to assess the preservation degree of H. inflatus (d'Orbigny, 1835) in representative environments across the base of the southeastern Mediterranean margin (cold water coral, active seepage pockmark and deep sea channel areas). In some core intervals, yellowish, recrystallized internal molds of this species are present. They have been previously observed in the Eastern Mediterranean, but the nature and origin of their colour was never explained. Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS) and Electron Backscatter Diffraction (EBSD) revealed that the recrystallized molds of the H. inflatus shells are formed by aragonite needles and high-Mg calcite crystals. The formation and preservation of these internal molds is induced by advective methane emissions, typically precipitating aragonite and High-Mg calcite phases close to the sediment–water interface. These molds were never used in previous applications of the LDX or in any existing ranking of pteropod preservation. Therefore, we have categorized these peculiar features combining previous pteropod ranking descriptions with the new observations to develop a modified biotic index (Heliconoides Modified Dissolution Index-HMDI). High values of the HMDI at the base of the pockmark core correspond to the interval where also active seepage-related features – e.g., bubble emissions, low-oxygen benthic foraminifera, chemosymbiotic molluscs, small fragments of authigenic carbonate crusts and slightly depleted δ13C values – occur, showing the ...